2018
DOI: 10.1080/00038628.2018.1461060
|View full text |Cite
|
Sign up to set email alerts
|

Sick building syndrome: are we doing enough?

Abstract: Health and well-being are vitally important aspects of people centric building design and are the roots of productivity. Sick building syndrome (SBS) is a collection of factors that can negatively affect physical health in several ways. Besides physical health is also related to psychological well-being because the human body is one interactive biological system. This paper focuses on reviewing the current state of knowledge on building sickness syndrome which has been prevalent as a building illness since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(113 citation statements)
references
References 185 publications
(223 reference statements)
3
83
0
6
Order By: Relevance
“…The review considered publication materials from various academic databases, namely Scopus, Google Scholar, and Web of Science. The application of multiple search engines to investigate the body of literature covers the weaknesses of one source by using the strength of others [25,26]. The approach to conducting the review consists of three main steps.…”
Section: Methodsmentioning
confidence: 99%
“…The review considered publication materials from various academic databases, namely Scopus, Google Scholar, and Web of Science. The application of multiple search engines to investigate the body of literature covers the weaknesses of one source by using the strength of others [25,26]. The approach to conducting the review consists of three main steps.…”
Section: Methodsmentioning
confidence: 99%
“…Inadequate indoor lighting affects both vision and the photobiological needs of synchronizing circadian rhythm, which impacts sleep and depression [69]. Well-designed lighting is one of the most important design elements to support an occupant's ability to perform daily tasks and decrease the level of disability associated with these impairments [68].…”
Section: Physiological Factorsmentioning
confidence: 99%
“…temperature or air quality [9]) of a specific space by its occupants. TC is studied because it has been shown that it favors not only the comfort, but also the wellness, the health, the productivity and the performance of the occupants of a space [13,19]. So, the research in this domain is aimed to determine parameters and variables to help upgrading the conditions of habitability and quality of specific spaces [19].…”
Section: Thermal Comfortmentioning
confidence: 99%
“…Concerning the space itself and its external environment, variables such as radial temperature and relative humidity are of importance, while regarding the occupants, variables of interest are for instance the body mass index and the level of isolation of thermal clothing [11,17,20]. Based on this discussion, the approaches for the study of Thermal Comfort are two [10,13,17,18]: Thermal Comfort involves then the analysis of a highly complex context, that can be easily influenced by a large number of aspects [10,17,19]. However, in spite of being a highly studied topic, it is commonly tackled with a traditional perspective.…”
Section: Thermal Comfortmentioning
confidence: 99%